2021 IEEE 21st International Conference on Bioinformatics and Bioengineering (BIBE) 2021
DOI: 10.1109/bibe52308.2021.9635238
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a noninvasive tongue-computer interface for individuals with severe disabilities

Abstract: Tongue-computer interfaces have shown the potential to control assistive devices developed for individuals with severe disabilities. However, current efficient tongue-computer interfaces require invasive methods for attaching the sensor activation units to the tongue, such as piercing. In this study, we propose a noninvasive tongue-computer interface to avoid the requirement of invasive activation unit attachment methods. We developed the noninvasive tongue-computer interface by integrating an activation unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…One-third of the disabled participants interviewed in a previous study reported that they were not interested in using the ITCI due to the need for a piercing (Caltenco et al, 2012). We presented a non-invasive approach of using the ITCI system in a pilot study (Kirtas et al, 2021), and this new method is still under development.…”
Section: Discussionmentioning
confidence: 99%
“…One-third of the disabled participants interviewed in a previous study reported that they were not interested in using the ITCI due to the need for a piercing (Caltenco et al, 2012). We presented a non-invasive approach of using the ITCI system in a pilot study (Kirtas et al, 2021), and this new method is still under development.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it does not get affect by spinal or cord injuries. As a result, it can serve as an alternative means of Control [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In [17], we developed a new noninvasive sensor activation method by mounting a frame with an integrated AU to the ITCI as a proof of concept for noninvasive tongue based robotic interfaces that does not require gluing or piercing an AU to the tongue. However, the current design of the ITCI with two angled positioned sensor PCBs only allows activating a portion of the sensors with a frame integrated AU.…”
Section: Introductionmentioning
confidence: 99%